Monitoring & evaluation for climate change adaptation: A synthesis of tools, frameworks and approaches - Bours, D; McGinn, C; Pringle, P (2013)
This report represents a synthesis and summary of frameworks for the monitoring and evaluation (M&E;) of climate change adaptation (CCA) interventions, with a specific focus on international development projects and programs. The objective of this report is to: • Provide an easy-to-read synthesis of current adaptation M&E; resources, frameworks, and approaches so that practitioners are able to more easily identify the information and tools that are most relevant to their needs. • Provide a short analysis of the “state of play” of adaptation M&E; guidance, identifying key themes and reflecting upon gaps and future priorities. We recognise that the resources reviewed here were developed for different, and sometimes specific, purposes. As a result, we have not sought to recommend or “score” tools, as their value and relevance will depend on the context in which they are applied. Instead, we have aimed to provide a subjective assessment of each resource in terms of its purpose, a summary of content and approach, its potential application, and the contribution it makes to our broader understanding of adaptation M&E.; We recognise that more work in this field is on-going, and that in some cases the resources reviewed in this report are also evolving. Consequently, this report provides a “snapshot” review at a given point in time.